2022
DOI: 10.3390/ijerph19138114
|View full text |Cite
|
Sign up to set email alerts
|

Classic Psychedelics and Human–Animal Relations

Abstract: Previous research has found associations between classic psychedelic use and nature-relatedness, but the link between classic psychedelic use and human–animal relations remains largely unexplored. Using data representative of the US adult population, with regard to age, sex and ethnicity (N = 2822), this pre-registered study assessed lifetime classic psychedelic use, ego dissolution during respondents’ most intense experience using a classic psychedelic, and three measures related to human–animal relations: sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…As detailed in Table 2 , recent empirical literature links psychedelics to long-term increases in: Appreciation of nature ( Studerus et al, 2011 ), non-human animals ( Pöllänen et al, 2022 ), nature relatedness ( Nour et al, 2017 ; Lyons and Carhart-Harris, 2018 ; Kettner et al, 2019 ), and pro-environmental behavior ( Forstmann and Sagioglou, 2017 ); Esthetic appreciation ( Studerus et al, 2011 ; Noorani et al, 2018 ); Altruism and prosociality ( Griffiths et al, 2006 , 2008 , 2018 ; Schmid and Liechti, 2018 ); Appreciation of spirituality ( Griffiths et al, 2018 ); Reduced valuation of financial success ( Lerner and Lyvers, 2006 ); More liberal and less authoritarian political views ( Nour et al, 2017 ; Lyons and Carhart-Harris, 2018 ). …”
Section: Review Of Psychedelic Value Changes and Self-transcendent Va...mentioning
confidence: 99%
See 1 more Smart Citation
“…As detailed in Table 2 , recent empirical literature links psychedelics to long-term increases in: Appreciation of nature ( Studerus et al, 2011 ), non-human animals ( Pöllänen et al, 2022 ), nature relatedness ( Nour et al, 2017 ; Lyons and Carhart-Harris, 2018 ; Kettner et al, 2019 ), and pro-environmental behavior ( Forstmann and Sagioglou, 2017 ); Esthetic appreciation ( Studerus et al, 2011 ; Noorani et al, 2018 ); Altruism and prosociality ( Griffiths et al, 2006 , 2008 , 2018 ; Schmid and Liechti, 2018 ); Appreciation of spirituality ( Griffiths et al, 2018 ); Reduced valuation of financial success ( Lerner and Lyvers, 2006 ); More liberal and less authoritarian political views ( Nour et al, 2017 ; Lyons and Carhart-Harris, 2018 ). …”
Section: Review Of Psychedelic Value Changes and Self-transcendent Va...mentioning
confidence: 99%
“…Appreciation of nature ( Studerus et al, 2011 ), non-human animals ( Pöllänen et al, 2022 ), nature relatedness ( Nour et al, 2017 ; Lyons and Carhart-Harris, 2018 ; Kettner et al, 2019 ), and pro-environmental behavior ( Forstmann and Sagioglou, 2017 );…”
Section: Review Of Psychedelic Value Changes and Self-transcendent Va...mentioning
confidence: 99%
“…Furthermore, the investigation of additional variables related to pro-environmental concern such as awareness of the sixth mass extinction (Ceballos et al, 2015) or human-animal relations (Caviola et al, 2019) may be worthwhile. For example, a recent study on a large representative US sample found that lifetime psychedelic use predicts positive human-animal relations, most likely via psychedelic induced ego dissolution (Pöllänen et al, 2022). That said, administration studies should increasingly focus on understanding psychedelics’ mechanism of action in order to understand what causes the connectedness.…”
Section: Discussionmentioning
confidence: 99%
“…These effects could be due to the mystical-type experiences (Kangaslampi et al, 2020) and feelings of ego dissolution (Kettner et al, 2019; Nour et al, 2017; Pöllänen et al, 2022; Uthaug et al, 2018) that psychedelics induce, as they were strong correlates of the increase in the individual's relationship to nature following a psychedelic experience. In line with these findings, psilocybin administration studies found dose-dependent increases on self-reported external unity, that is, feelings of interconnectedness with objects from the external world (Griffiths et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Conscious and responsible use of psychedelic plant medicines like ayahuasca and psilocybin can also be fruitful options. Psychedelic use predicts nature connectedness (Nour et al, 2017 ; Kettner et al, 2019 ), and solidarity with other species (Pöllänen et al, 2022 ), translating into pro-environmental behaviour (Forstmann and Sagioglou, 2017 ), as well as both concern for and objective knowledge about climate change (Sagioglou and Forstmann, 2022 ), while a recent survey on “psychedelically induced biophilia” found a tendency to elicit a “passionate and protective” connection with nature (Irvine et al, 2023 ). Engagement with these practices would also encourage interaction with cultures from which they originate, affording opportunities for learning from and cooperation with indigenous peoples who currently steward lands with 80% of the world's biodiversity (Watene and Yap, 2015 ), and increasingly carry the flame for cultural diversity and lost ecological wisdom (Toledo, 2013 ; Rowlandson, 2015 ; Etchart, 2017 ; George et al, 2019 ).…”
Section: Human Behaviour As An Aspect Of Gaiamentioning
confidence: 99%